A Reasonable Evaluation of Chuanxiong Rhizoma Processing with Wine through Comparative Pharmacokinetic Study of Bioactive Components: Dominant Effect on Middle Cerebral Artery Occlusion Model Rats - Ke Pei; Lilong Cao; Gang Cao; Hao Cai; Yan Ning; Tingting Zhao; Lin Sun; Haixin Liu; Shuosheng Zhang (Journal of Analytical Methods in Chemistry)
According to the ancient documents and Chinese herbal medicine processing experience, Chuanxiong Rhizoma was usually processed with yellow rice wine to improve efficacy. However, the relevant mechanisms are still unclear so far. In this study, a validated ultrahigh-performance liquid chromatography tandem mass spectrometry method was used to compare the pharmacokinetics of four representative components in middle cerebral artery occlusion rats after oral administration of raw and wine-processed Chuanxiong Rhizoma. The neurobehavioral scores and 2,3,5-triphenyltetrazolium chloride staining were employed to evaluate the model. Biological samples were prepared by protein precipitation with methanol. All analytes were separated on an ACQUITY BEH C18 column through gradient elution using acetonitrile and 0.01% of formic acid as mobile phase, and the flow rate was 0.3 mL/min. The results showed that the maximum plasma concentrations, the area values under the concentration-time curves of senkyunolide A, and ferulic acid in wine-processed Chuanxiong Rhizoma were all higher than in raw Chuanxiong Rhizoma, which were completely opposite to our previous studies in normal rats. Compared with normal rats, the theory that wine processing could enhance the efficacy of Chuanxiong Rhizoma may be better reflected in model rats.